Terriorist bombings: Motives, methods and patterns of injuries - Morley, B.; Leslie, Gavin (Elsevier, 2007)
Summary Terrorism is an act of violence, mostly directed at civilian populations, and aimed at inflicting mass casualties. The motives of terrorists are political, and emanate from groups who desire political or religious change or revenge, yet lack the political power to enforce the change through any means other than violence. Unlike criminal groups, terrorists seek to gain maximum public attention to the point of claiming responsibility for their acts. Of all the forms of terrorism, bombing has become the most common and presents a high degree of risk for any nation. From 1969 to 1983, 200 terrorist bombings occurred world-wide. However, over the following 10 years terrorist bombings increased more than 15-fold [Dire D, Gatrell C, Conventional terrorist bombings. In: Hoogan D, Burnstein J, editors. Disaster medicine. Sydney: Lippincott Williams & Wilkins; 2002. p. 301—16]. Bombing poses a specific spectrum of injuries. Although they can inflict mass casualties, most casualties suffer only minor injuries and do not require hospitalisation. Yet for those close to the blast the injuries sustained are complex, multiple and severe. This paper discusses the motives and methods of terrorists and examines some of the issues, which have determined the nature of terrorism. The paper focuses on bombing as a terrorist tactic and discusses the physics of bomb blasts, and the resultant spectrum of injuries and outcomes.